Genetic and behavioural data confirm the existence of a distinct harbour porpoise ecotype in West Greenland - Olsen, Morten Tange; Nielsen, Nynne Hjort; Biard, Vincent; Teilmann, Jonas; Ngô, Mạnh Cường; Víkingsson, Gísli; Gunnlaugsson, Thorvaldur; Stenson, Garry; Lawson, Jack; Lah, Ljerka; Tiedemann, Ralph; Heide-Jørgensen, Mads Peter (Ecological Genetics and Genomics, 2022)
Elucidating the evolutionary and ecological characteristics of distinct populations constitutes a cornerstone in the classification of ecotypes, and in assessing their specific responses to environmental changes and potential impacts from human activities. In this study, two complementary approaches were deployed to investigate the existence of a putative harbour porpoise (Phocoena phocoena) ecotype in West Greenland. Genetic differentiation of 68 porpoises from West Greenland, and neighbouring Canada and Iceland were studied by ddRADseq analysis, and 18 porpoises instrumented with satellite transmitters were used to study their movement behaviour and site fidelity. The results suggest a genetically distinct harbour porpoise population in West Greenland, with strong site fidelity during the August breeding period and wide-ranging dispersal in the North Atlantic at other seasons. This adds to previously described unique characteristics of West Greenland harbour porpoises, including mesopelagic foraging behaviour, distinct skull morphology and tooth ultrastructure, and shorter, yet heavier, body; all pointing to the existence of a distinct West Greenland ecotype. We hypothesize that this ecotype arose through gradual adaptation to the local environmental conditions of the West Greenlandic shelf area, including high summer primary productivity and seasonal sea ice coverage. Consequently, this distinct ecotype of harbour porpoises necessitates a focused conservation plan.